A SERVQUAL based E-Commerce platform for Indian customers - Billewar, Dr. Satish R.; Ghane, Prof. Sunil; Londhe, Dr Gaurav; Saxena, Prof. Sunil (The journal of contemporary issues in business and government, 2021)
The customer reviews and ratings are now part of the purchasing process on E-Commerce platforms. It helps online businesses from knowing the goods but also influences companies to rectify the lacunas in buying process and to give better services to the customers. Nevertheless, poor reviews are a great deal to enhance the quality of the goods and services. That means a lot for the improvement of the products is needed. Most of the time bad reviews and ratings are outcomes of the problems faced by the customer after the delivery of the products. The customer expects a repair facility after the warranty period of the products. Often customers expect the repair facility like a service engineer to be close to their home. The key issue is that there is no shared forum to provide all of the product services. Online businesses must consider the effect of the psychology of the customers on their company. The paper recommends SERVQUAL for improvements in Indian E-Commerce like pre-purchase product comparisons, repair facility to every product after warrantee, and a helpdesk with a real-time conversation facility to resolve the issues in services for any brands in the existing E-Commerce structure based on customer’s reviews and ratings only.